Resilience for food security in refugee-hosting communities - Mabiso, Athur; Maystadt, Jean-François; Vandercasteelen, Joachim; Hirvonen, Kalle (International Food Policy Research Institute, 2014)
There is a strongly held view that a narrow window exists for effective nutritional interventions and a widely known stylized depiction of age‐dependent economic rates of returns to investments in cognitive and socioemotional development. Both indicate critical periods in early life. Moreover, the fact that both the physical and cognitive development of a child in these early years are highly dependent on childcare practices and on the characteristics of the caregivers motivates an interest in finding effective means to enhance stimulation in the context of nutritional programs, or vice versa. Nevertheless, there is relatively little evidence to date on how to align integrated interventions to these age‐specific patterns and how to undertake benefit–cost analyses for integrated interventions. Thus, many core questions need further consideration in order to design integrated nutritional and stimulation programs. This paper looks at some of these questions and provides some guidelines as to how the economic returns from joint nutrition and stimulation programs might be estimated.